Contemporary capitalism and production of subjectivities from Deleuze’s perspective (Devenires, 2018)
We present current theories pointing to the relationship between political-economic and subjective production. We take up ideas from Deleuze, Guattari, Berardi and Lazzarato, who stress the importance of the analysis of subjective production to understand the crises of capitalism, and its production of failed subjectivities as life models – for example, the successful entrepreneur or the cognitive worker, which result in images of an indebted person or one mired in substance dependence. What is the relationship between economics and subjectivity in the workings of contemporary capitalism? What myths or subjective models has capitalism tried to invent lately? What critical tools do we have in order to think forms of subjectivity that escape capitalist models?
Keywords: subjectivity; capitalism; production; model; economic psychology